Intraparenchymal schwannoma with calcification of the temporal lobe: Case report and literature review. Issue 4 (January 2019) - Chen, Fan; Zhao, Shuai; Yu, Ying; Chen, Dawei
Abstract: Rationale: Intracranial schwannomas most frequently arise from the trigeminal nerve and the vestibular nerve. Schwannomas within the cerebral parenchyma are exceedingly rare. Additionally, calcification is an uncommon histopathological and radiological characteristic in schwannomas. Patient concerns: A 46-year-old man presented to us with sudden onset epileptic seizure and a 3-month history of intermittent headache. After admission, the physical and neurological examinations were all normal. Brain CT revealed an irregular, well-defined, hyperdense mass in the right temporal lobe. MRI showed a solid mass appearing iso- to hypointensity on T1-weighted imaging and heterogeneous intensity on T2-weighted imaging in the right temporal lobe; after Gd-DTPA administration, the lesion showed heterogeneous enhancement. Diagnosis: Histopathological examination revealed hyperchromatic nuclei and loose intercellular matrix with calcification. Immunohistochemical analysis demonstrated that the tumor was strongly positive for S100 protein but negative for GFAP and CK, which was consistent with a schwannoma. Interventions and outcomes: A surgical resection via the right temporal approach was performed. Intraoperatively, we noticed that the tumor was grayish yellow, capsuled, and located entirely within the temporal parenchyma. A gross total resection was achieved. The postoperative course was uneventful, and there was no epileptic seizure. Lessons: Intraparenchymal schwannoma with calcification is an uncommon histopathological and radiological characteristic in schwannomas. Intraparenchymal schwannoma with calcification is extremely rare. The early identification and appropriate surgical treatment should be highlighted.